Imaging of the Postoperative Condition of Posterolateral Corner Injuries - Naraghi, Ali; Pearce, Dawn H.; Whelan, Daniel B.; Chahal, Jaskarndip (Seminars in Musculoskeletal Radiology, 2018)
Posterolateral corner (PLC) injuries of the knee are often sustained in combination with anterior or posterior cruciate ligament injuries. A variety of surgical techniques including acute repair, nonanatomical reconstructions, and anatomical reconstructions have been used to treat grade III PLC injuries. Scant literature is available on postoperative imaging of the PLC. This article reviews the more commonly used surgical techniques and the postoperative imaging assessment of the PLC of the knee.
Keywords: postoperative; posterolateral corner knee; MRI